1988
DOI: 10.1128/jcm.26.11.2361-2366.1988
|View full text |Cite
|
Sign up to set email alerts
|

Annual incidence, epidemiology, and comparative in vitro susceptibilities to cefoxitin, cefotetan, cefmetazole, and ceftizoxime of recent community-acquired isolates of the Bacteroides fragilis group

Abstract: The six species of the Bacteroides fragilis group are potent pathogens and commonly have different susceptibility patterns. We determined the relative annual isolation rate of anaerobic bacteria and the susceptibility of B. fragilis group species isolated during 1987 at two community hospitals. The relative frequencies of isolation of 261 strains were as follows: B. fragilis, 61%; B. thetaiotaomicron, 17%; B. distasonis, 7%; B. vulgatus, 6%; B. ovatus, 5%; and B. uniforms, 4%. A total of 234 recent clinical is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(9 citation statements)
references
References 24 publications
2
7
0
Order By: Relevance
“…In our study, only 6% of organisms could not be identified by BioFire BCID since they were not found on the panel. The spectrum of causative pathogens and the sources of infection for the NB-PC group in our study corresponded to that reported in the literature (18)(19)(20). In our study, the organisms from the NB-PC cohort that were determined to be true pathogens were mostly Bacteroides spp., followed by Clostridium and Fusobacterium spp.…”
Section: Discussionsupporting
confidence: 86%
“…In our study, only 6% of organisms could not be identified by BioFire BCID since they were not found on the panel. The spectrum of causative pathogens and the sources of infection for the NB-PC group in our study corresponded to that reported in the literature (18)(19)(20). In our study, the organisms from the NB-PC cohort that were determined to be true pathogens were mostly Bacteroides spp., followed by Clostridium and Fusobacterium spp.…”
Section: Discussionsupporting
confidence: 86%
“…The occurrence of anaerobic and aerobic bacteraemias at the University Hospital Basel (UHBS), Switzerland, was estimated, and the proportions of six important groups of anaerobes in relation to 1000 blood cultures as well as in relation to positive aerobic blood culture results over a 10-year period were analyzed [17]. [18] determined the relative annual isolation rate of anaerobic bacteria and the susceptibility of B. fragilis group species isolated during 1987 at two community hospitals in Los Angeles, California, US. The relative frequencies of isolation of 261 strains were as follows: B. fragilis, 61%; B. thetaiotaomicron, 17%; B. distasonis, 7%; B. vulgatus, 6%; B. ovatus, 5%; and B. uniformis, 4%.…”
Section: Discussion and Review Of Literaturementioning
confidence: 99%
“…The relative frequencies that the various species were encountered at the Wadsworth Veterans Administration Medical Center are presented in Table 1. The data presented in Table 1 for the R. M. Alden Research Laboratory were compiled in a previous study (9).…”
Section: Resultsmentioning
confidence: 99%
“…Anaerobes are potent opportunistic pathogens and can be isolated from any type of infection. More than one-third of all anaerobes isolated from clinical specimens are members of the Bacteroides fragilis group, and the species B. fragilis is the anaerobe most frequently isolated from blood cultures (9). The pathogenicity of the B. fragilis group is related to a variety of virulence factors, including proteolytic and hydrolytic enzymes and capsules that differ among Bacteroides species (3,15,19,22).…”
mentioning
confidence: 99%